FRI0401 Initial manifestation determines clinical entity and course in patients with anti-centromere antibody: a single center longitudinal retrospective cohort study. (15th June 2017) - Tsukamoto, M; Suzuki, K; Seta, N; Takeuchi, T
Abstract : Background: Anti-centromere antibody (ACA) is often detected in sera from autoimmune diseases, such as limited cutaneous systemic sclerosis (SSc) and primary biliary cirrhosis (PBC). ACA-positive Sjögren's syndrome (SjS) is recently considered as a distinct clinical subgroup in SjS [1–2]. The other autoimmune diseases associated with ACA-positive have not fully elucidated and the role of ACA in their pathogenesis still remains unclear. In addition, comprehensive and enough clinical information from the point of view of ACA positive cases has not been accumulated. Objectives: To clarify clinical features of patients with ACA and their association with autoantibodies. Methods: Patients with discrete-speckled pattern in anti-nuclear antibody (ANA) test and/or positive ACA, who visited to our department during over 20 years between May 1995 and December 2016, were enrolled. Clinical information and immunological tests including immunoglobulin (Ig) and serum autoantibodies were collected and statistically analyzed. Results: Discrete-speckled pattern in ANA test and/or positive ACA were identified in 309 patients. There were 292 female and 17 male and the average age was 60 years old. Proportion of concomitant ANA patterns were speckled (16%), homogenous (7%), cytoplasmic (3%) and/or nucleolar (3%) pattern. 186 patients (60%) had Raynaud's phenomenon and 149 patients (48%) had sclerodactyly. 162 patients (52%) had oral and/or ocular dryness symptoms. 21 patients (6%) had interstitial pneumonia and 13 patients (4%) had pulmonary hypertension. 42 patients (13%) had arthritis. 19 patients (6%) had thyroid disease. 214 patients (69%) were classified into 17 autoimmune diseases (including overlap cases) from symptoms at initial visit, while other 95 patients (31%) who did not meet the criteria were not diagnosed. IgG, IgM and IgA in the patients who were classified into autoimmune diseases were higher than that in other patients who were not classified (p=0.0007, p=0.0057 and p=0.0158, respectively). In the 214 patients (69%), there were most of patients who were diagnosed as SSc (n=113, 36%) and/or SjS (n=78, 25%). 25 patients (8%) and 22 patients (7%) were diagnosed with rheumatoid arthritis (RA) and PBC, respectively. On the other hand, the patients who diagnosed as systemic lupus erythematosus were 3 (1%), and nobody was diagnosed as myositis. The mean observation period was 80 months. 2 patients in 95 patients who were unclassified at initial visit were diagnosed as RA or autoimmune hepatitis by developing new symptoms during observation. A patient was newly diagnosed as SSc in addition to SjS because sclerodactyly was newly developed. In other patients, the diagnosis was not changed and added during observation. Conclusions: Our single center longitudinal retrospective cohort study confirmed that ACA-positive cases were classified into various types of autoimmune disease. Few patients had new symptoms during observation but the initial diagnosis was unchanged. Our data demonstrated that initial manifestation determined clinical entity and course in patients with ACA. References: J Rheumatol 2001; 28: 2238. Int J Rheum Dis 2015; 18: 776. Disclosure of Interest: None declared